Socio-Economic Constraints of Home Modification to Mitigate the Risk of Falls among the Elderly in the Diverse Regions of Thailand - Chindapol, Sumavalee (Journal of Architectural/Planning Research and Studies (JARS), 2025)
This research highlights the inequality arising from socio-economic constraints in implementing home modifications to mitigate fall risks among the elderly. The study provides significant evidence of the complex association between low socio-economic status (SES) and its limitations in adopting fall prevention strategies, particularly in rural areas such as northern and northeastern Thailand. The SES related to home modifications for mitigating fall risks among the elderly was assessed through the three factors of house conditions, styles, and amenities. Houses in rural and urban areas were compared to highlight disparities in fall risk and the capacity to implement modifications. This research shows that fall risk in rural areas was significantly higher than in urban areas (p = 0.03), and SES in rural areas such as the north and the northeast was significantly lower than in more urbanised areas (p < 0.00). Furthermore, all three SES factors show a significant relationship with the incidence of falls (p < 0.00). Home modification construction cost can be categorised into three levels based on cost and scope: minor (24,000 Baht or 750 USD in 2021), moderate (30,500 Baht or 953 USD in 2021), and major (47,000 Baht or 1,469 USD in 2021). Major modifications as part of the research project covering structural renovations included reinforcement and replacement which accounted for 41% of the total construction cost, while costs for universal design equipment constituted 34% of the total construction cost. A key contribution of this study is the identification and quantification of specific socio-economic constraints that limit home modifications in rural areas of Thailand. The most significant constraints include financial limitations, poor housing conditions, and limited access to technical knowledge for modifying specific local housing conditions and styles. This research frames these constraints as critical barriers to achieving safe living environments for the elderly, particularly before universal design can even be applied. By offering a classification of home modification needs linked to socio-economic capacity and advocating for an increase in current government construction subsidies, —including labour costs—by at least 10%, the study provides a practical framework for assessing readiness and challenges in real-world aging in place settings.